Adult Attachment and Personality Traits and the Quality of Marriage of Husband and Wife Couples - Yuspendi Yuspendi; Fun-Fun Lie; Cindy Maria (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2015)
The study aimed to increase the quality of marriage by understanding the match between adult attachment and personality traits (which includes agreeableness, conscientiousness, and neuroticism) on marriage quality of couples. Five hundred couples or 1000 participants were recruited with cluster area sampling in five areas of Bandung City, and were asked to complete Marital Satisfaction Scale and Big Five Inventory. Data was analysed using Multiple Regression and Paired-Sample T-Test. Results showed that adult attachment and personality traits both had a simultaneous effect on marriage quality. Adult attachment had a greater effect compared to the three traits mentioned. Agreeableness was found to have a direct effect on marriage quality of couples, while conscientiousness was found to only have a direct effect on husbands, not wives. Neuroticism was not found to have any direct effects on marriage quality. Further paired sample t-test result confirmed these findings.